Relationship between the product differentiation and firm performance of Japanese invested enterprises (JIEs) in Vietnam - Le, Thi Thu Ha; Ho, Thi Thu Quynh (Journal of International Economics and Management, 2016)
The amazing proliferation of product choices as well as remarkable improvements in innovation activities during recent decades have become key driving forces of product differentiation, which is deemed as a sustainable competitive advantage of firms in technological-driven economy. The concept of product differentiation in this paper will be approached from innovation perspective, referring to capabilities of firms to enhance product quality, design, and unique features. In addition, firm performance is measured comprehensively through Balanced ScoreCard (BSC). Utilizing survey data from 158 JIEs operating in Vietnam, this study finds out the positive association between product differentiation and firm performance in both manufacturing and service industry. Unique product feature is examined to be the most important determinant of product differentiation affecting performance of JIEs, which should be prioritized in sustainable development of JIEs.